Experiências de enfermeiras da atenção primária à saúde na consulta em puericultura - Bugs, Cíntia Vanuza Monteiro (2023)
Childcare nursing consultation is a strategy for monitoring and follow-up children's health. The nurse who works in Primary Health Care (PHC) has the following duties: care and health education actions aimed at child growth and development, support for breastfeeding, control of immunizations, sleep, hygiene and accident prevention. The consultation reflects on the promotion of child health and prevention of health problems, for this reason, this practice needs to be conducted in a qualified manner for the healthy growth and development of the child. General Objective: to understand the experience of PHC nurses in childcare consultations. Specific objectives: discuss barriers and facilitators for development of childcare consultation and strategies for its qualification in the experience of PHC nurses. Method: Qualitative research. Data collection occurred using the Focus Group technique, after approval by the Research Ethics Committee of the Federal University of Santa Maria under CAAE number 67681123.1.0000.5346 and opinion number 5,969,876. Six face-to-face meetings were held with twelve nurses working in PHC in a municipality in the Central region of Rio Grande do Sul. Thematic Content Analysis was used to analyze the data. Results: Three thematic categories emerged. Elements and circumstances that facilitate nursing consultations in childcare: use of materials from Ministry of Health to conduct the consultation, interspersed care with a doctor and multidisciplinary team, bond and trust in the consultation carried out by the nurse since prenatal care, adequate physical structure and available materials, use of social media to publicize actions. Barriers to nursing consultations in childcare: lack of understanding among pacients and healthcare team about the importance of consultation and the nurse's work, multiparity, preference for consultation with pediatrician, large territories areas and a high children's demand for childcare, nurse overload, inadequate physical structure and precarious or unavailable materials, complexity of childcare consultations, scarcity of continuing education actions in Child Health. Strategies for development of childcare nursing consultations: dissemination of successful actions involving childcare advertising on social media, creation of support materials to guide consultations such as a website, checklist, videos and serial albums, continuing education and qualify professionals with workshops and conversation circles. Final considerations: facilitators, barriers and strategies based on experience will enable the (re)organization of priorities and behaviors to improve childcare care. For health professionals, especially Nursing, this study reinforces the need to continuously execute the professional qualification process for development of a childcare consultation based on scientific knowledge, aligned with different contexts of services and realities of children and their families.